Étienne Gilson and 20th Century Linguistics: The Mystery of Signification as a Task for Philosophy - Casillo, Felicitas (Scripta Mediaevalia, 2025)
In Linguistique et Philosophie: Essai sur les constantes philosophiques du langage (1969), Étienne Gilson discusses some of the most influential theses in 20th-century linguistics. This article primarily focuses on Gilson’s critique of the contributions made by linguists Ferdinand de Saussure, Émile Benveniste, and Noam Chomsky. From an Aristotelian perspective, Gilson highlights both the achievements and limitations of these theories, arguing that the phenomenon of meaning cannot be fully understood without engaging with philosophy. According to Gilson, language is not merely a system of arbitrary signs, composed of numerous elements and rules, but it also requires a metaphysical inquiry, which linguistics has tended to ignore or underestimate.